Architecture antique entre âge du Fer et époque impériale en Provence : les piliers du site de Château-Bas à Vernègues - Sandrine Agusta-Boularot; Raphaël Golosetti (Gallia)
The site of Château-Bas (Vernègues, Bouches-du-Rhône), famous above all for its Augustan Roman temple, has yielded a set of pillars decorated either with writhing snakes or with straight rods. As yet there are no known parallels to such pillars. The discovery of a fragment of a pillar reused in a 1st c. AD structure demonstrates that these carvings are ancient. The architectural study of the fragments and comparison with other sculptural elements from southern Gaul suggest they date approximately to the turn of the millenium. The originality of these pieces should perhaps be sought in the copying and adaptation of Italic architectural features (Attic base, Tuscan capital) to a particular form of monument (pillar, stela) and type of decoration (snake) attested in Provence in the Late Iron Age.